In Vitro Antifungal Activity of Plain Socks and Zinc Oxide Nanoparticle-Coated Socks - Prasong W. (2023)
BACKGROUND: Fungal foot infection is a common superficial fungal infection and is recognized as an important public health problem. Related to the wearing of occlusive footwear, foot infection is usually caused by dermatophytes and nondermatophyte molds. Previous in vitro studies have demonstrated that zinc oxide nanoparticles (ZnO-NPs) have antimicrobial activity against fungi. This study, therefore, evaluated the ability of socks coated with ZnO-NPs to inhibit fungal growth in an in vitro model mimicking real-life situations. METHODS: Scale from patients with fungal foot infections was equally divided into three groups: control, plain socks, and ZnO-NP socks. The specimens in the control group were routinely fungal cultured, whereas in the plain sock and ZnO-NP sock groups, scale was incubated with plain socks and ZnO-NP socks, respectively, for 24 hours. After incubation, each piece of sock was cultured. The fungal culture results of the three groups were progressively evaluated for 4 weeks. RESULTS: From 31 specimens, the positive fungal culture results of the control, plain sock, and ZnO-NP sock groups were 100%, 64.5%, and 54.8%, respectively. Specimens incubated with plain socks (P = .001) or with ZnO-NP socks (P < .001) had a significant reduction in the number of positive fungal cultures compared with the control. CONCLUSIONS: Plain socks and ZnO-NP socks significantly inhibited fungal growth relative to the control. The wearing of either plain socks or ZnO-NP socks can prevent fungal foot infection because these socks act as a barrier to the insoles of shoes.